Theoretical and legal basis of improving anti-smuggling: certain current aspects - Kovalyova, Maryna; Shevchenko , Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article examines the theoretical and legal principles and features of legal responsibility for combating smuggling. The expediency of revising the theoretical and legal foundations is explained by the rapidity of the introduction of changes in the Ukrainian legislation on combating smuggling and strengthening legal responsibility for smuggling. The legal regulation of the criminalization of smuggling according to draft law №5420, which provides for criminal liability for the smuggling of goods in significant and large quantities, as well as for the false declaration of goods, in particular, committed with a prior collusion with a customs official, was studied. During the analysis of draft law №5420, it was determined that the strengthening of legal responsibility for smuggling as a tool for combating it is quite radical and will contribute to greater «toughness» of control for subjects of foreign economic activity. The existing redundancy regarding the strengthening of responsibility for economic violations of today is not particularly necessary at the moment, since taking into account the burden on customs authorities, the emergence of the criminalization of smuggling will only further force customs authorities to conduct a significant number of inspections of subjects of foreign economic activity, which will undermine the trust of national businesses in customs and will significantly affect the amount of turnover and the stability of Ukraine’s foreign economic policy. The available statistical data make it clear that any conditions do not prevent the commission of contraband offenses in order to avoid payment of customs payments and other taxes to the state budget. Thus, approaches to the criminalization of smuggling should be gradual and have an appropriate balance of legal qualifications between administrative and criminal law.